2015
DOI: 10.1039/c5ta01285f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic interaction between platinum nanoparticles and nitrogen-doped reduced graphene oxide: effect on the oxygen reduction reaction

Abstract: Confirmed by DFT, a significant amount of platinum atoms are chemically bound to N of N-doped RGO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 69 publications
(87 reference statements)
8
139
0
1
Order By: Relevance
“…The 2D and the D+G bands are also visible with small intensity at around 2700 and 2930 cm −1 , respectively. The results are consistent with previously reported Raman spectra of graphene oxide and nitrogen-doped graphene sheets [28]. The ID/IG ratio slightly increased after the thermal treatment of GO from 0.91 to 1.05 due to the increase in the number of structural defects caused by the incorporation of nitrogen atoms into the carbonaceous framework.…”
Section: Electrochemical Measurementssupporting
confidence: 92%
See 3 more Smart Citations
“…The 2D and the D+G bands are also visible with small intensity at around 2700 and 2930 cm −1 , respectively. The results are consistent with previously reported Raman spectra of graphene oxide and nitrogen-doped graphene sheets [28]. The ID/IG ratio slightly increased after the thermal treatment of GO from 0.91 to 1.05 due to the increase in the number of structural defects caused by the incorporation of nitrogen atoms into the carbonaceous framework.…”
Section: Electrochemical Measurementssupporting
confidence: 92%
“…There is a considerable amount of oxidized platinum, which is likely the result of the smaller size of the platinum nanoparticles. A high percentage of Pt atoms on the nanoparticle surface in contact with air gives rise to different oxide phases [28]. This kind of interaction could increase the electrocatalytic activity and durability of ORR catalysts.…”
Section: Fig 2 N 1s (A-c) and Pt 4f (D-f)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although they could lead to excellent durability performance via stabilizing and steric effect, the confined Pt NPs in carbon surface layer will sacrifice a large proportion of active sites [19,20]. It is reported that the carbon support containing nitrogen groups can allow for the homogenous embedding of Pt NPs, facilitating electrons to transfer from Pt to carbon support, and the robust interaction between Pt and N atoms endows the catalysts with enhanced electrochemical activity and even durable catalytic performance [16,21]. Therefore, achieving Pt NPs homogeneously embedded in N-doped carbon materials through a facile and environment-friendly method is important for the electrochemical catalysts in energy conversion and storage technologies.…”
Section: Introductionmentioning
confidence: 99%